INTEGRASI SAINS DENGAN AGAMA DAN PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF NIDHAL GUESSOUM - Husni Mubarok; Amril Mansur (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to determine the integration of science with religion and Islamic educational thought from Nidhal Guessoum's perspective. The research method used is library research. The results of the research show that: a) Nidhal Guessoum's work consists of approximately 8 book titles, one of which is quite popular in Indonesia, namely Islam's Question Reconciling Muslim Tradition and Modern Science (2011), with the Indonesian title "Islam and Modern Science" ( 2015), The Determination of Lunar Crescent Month and The Islamic (1993), The Story of The Universe (2002), and Kalam is Necessary Engagement with Modern Science (2011). b) Nidhal Guessoum's thought builds an understanding of God in terms of Islamic philosophy as well as science, c) Nidhal Guessoum's school of thought embeds principles to support his quantum method in the form of theistic falsification principles which are scientific methodologies. Islamic scientific treasures are not passive, they will continue to be dynamic, experience progress and always carry out reconstruction as a responsibility to face the demands of the realities of life. For this reason, Nidhal Guessoum's thinking is very full of contextual-falsificative typology, and e). Implications of Nidhal Guessoum's ideas in Islamic education.